2022
DOI: 10.1155/2022/1850033
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of the Effect of TTM-Based Health Information Behavior Combined with Continuous Nursing on Cognitive and Motor Function, Living Ability, and the Quality of Life of Cerebral Stroke Patients

Abstract: Purpose. To discuss the effect of the transtheoretical model (TTM) of behavior-based health information behavior combined with continuous nursing on cognitive function, motor function, living ability, and quality of life of cerebral stroke (CS) patients. Methods. 540 cases of CS patients hospitalized in our hospital from June 2020 to June 2021 were selected. All the subjects were divided into the control group (270 cases) and study group (270 cases) according to the random number table. The control group was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is supported by previous studies. For example, a quasi-experimental study conducted continuous nursing based on the transtheoretical model of behavior and found signi cant improvement in living ability at 6 months post-discharge (Wu et al, 2022). Another study used a 12-week home-based transitional care model to facilitate patients to perform home-based exercises with continued monitoring and gradual progression in stroke survivors, leading to signi cant improvements in activities of daily living (Kam Yuet Wong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies. For example, a quasi-experimental study conducted continuous nursing based on the transtheoretical model of behavior and found signi cant improvement in living ability at 6 months post-discharge (Wu et al, 2022). Another study used a 12-week home-based transitional care model to facilitate patients to perform home-based exercises with continued monitoring and gradual progression in stroke survivors, leading to signi cant improvements in activities of daily living (Kam Yuet Wong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%